2015
DOI: 10.1080/15287394.2015.1067503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytotoxicity and Sperm Motility Using a Computer-Aided Sperm Analysis System (CASA) for Isomers of Phthalic Acid, a Common Final Metabolite of Phthalates

Abstract: The general population is exposed to phthalates through consumer products, diet, and medical devices. Phthalic acid (PA) is a common final metabolite of phthalates, and its isomers include isophthalic acid (IPA), terephthalic acid (TPA), and phthalaldehyde (o-phthalic acid, OPA). The purpose of this study was to investigate whether PA and PA isomers exert reproductive toxicity, including altered sperm movement. In vitro cell viability assays were comparatively performed using Sertoli and liver cell lines. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
5
0
4
Order By: Relevance
“…Daha önce yapılan çalışmalarda, birçok doku ve organı etkileyen bu kimyasalın üreme dokuları üzerine de toksik etkisinin olduğu rapor edilmiştir (16)(17)(18)21). Nitekim in vivo olarak değişik dozlarda uygulanan DEHP'in ratlarda (21), farelerde (17,18) ve boğalarda (26) testis dokusunda hasara neden olduğu ve testis ağırlığını düşürdüğü bildirilmiştir. Ayrıca DEHP maruziyetinin spermatozoon üretim merkezi olan seminifer tubulleri hasara uğrattığı (19), spermatozoon depolama ve taşıma bölümleri olan epididimis ve vas deferens hücreleri üzerine sitotoksik etkiye neden Fertilizasyonun başarıya ulaşmasında spermatozoonun hareketliliği ve sahip olduğu organallerin fonksiyonlarını yeterli düzeyde yerine getiriyor olması oldukça önemlidir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Daha önce yapılan çalışmalarda, birçok doku ve organı etkileyen bu kimyasalın üreme dokuları üzerine de toksik etkisinin olduğu rapor edilmiştir (16)(17)(18)21). Nitekim in vivo olarak değişik dozlarda uygulanan DEHP'in ratlarda (21), farelerde (17,18) ve boğalarda (26) testis dokusunda hasara neden olduğu ve testis ağırlığını düşürdüğü bildirilmiştir. Ayrıca DEHP maruziyetinin spermatozoon üretim merkezi olan seminifer tubulleri hasara uğrattığı (19), spermatozoon depolama ve taşıma bölümleri olan epididimis ve vas deferens hücreleri üzerine sitotoksik etkiye neden Fertilizasyonun başarıya ulaşmasında spermatozoonun hareketliliği ve sahip olduğu organallerin fonksiyonlarını yeterli düzeyde yerine getiriyor olması oldukça önemlidir.…”
Section: Discussionunclassified
“…Nitekim sığırların süt ve yağ dokusu gibi bazı dokularında DEHP tespit edildiği bildirilmiştir (23,24). Daha önce yapılan çalışmalarda, birçok doku ve organı etkileyen bu kimyasalın üreme dokuları üzerine de toksik etkisinin olduğu rapor edilmiştir (16)(17)(18)21). Nitekim in vivo olarak değişik dozlarda uygulanan DEHP'in ratlarda (21), farelerde (17,18) ve boğalarda (26) testis dokusunda hasara neden olduğu ve testis ağırlığını düşürdüğü bildirilmiştir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Results from the literature are divergent on the toxicity of PA. Ema et al observed that this chemical is not toxic to pregnant rats and their litter, while Kwack & Lee stated that it decreased the viability of testicle cells by 40% at 100 mM, a concentration 10× higher than the one that caused cell death in our experiment [43,44]. The present study is the first to assess the toxic effects of PA on proliferating lung cells, which is of extreme importance, since, as a by-product of naphthalene, it is present in the air in urban areas.…”
Section: Discussionmentioning
confidence: 45%